The blessings of liberty: human rights and religious freedom in the western legal tradition - Witte, John (Cambridge studies in law and Christianity, 2022)
Leading legal scholar John Witte, Jr. explores the role religion played in the development of rights in the Western legal tradition and traces the complex interplay between human rights and religious freedom norms in modern domestic and international law. He examines how US courts are moving towards greater religious freedom, while recent decisions of the pan-European courts in Strasbourg and Luxembourg have harmed new religious minorities and threatened old religious traditions in Europe. Witte argues that the robust promotion and protection of religious freedom is the best way to protect many other fundamental rights today, even though religious freedom and other fundamental rights sometimes clash and need judicious balancing. He also responds to various modern critics who see human rights as a betrayal of Christianity and religious freedom as a betrayal of human rights.